Total and acylated ghrelin plasma levels as potential long-term response markers in alcohol-dependent patients receiving high-dose of the GABA-B receptor agonist baclofen. (February 2019) - Geisel, Olga; Hellweg, Rainer; Wernecke, Klaus-Dieter; Wiedemann, Klaus; Müller, Christian A.
Highlights: Long term response to baclofen might be monitored by ghrelin assessments. Total ghrelin correlated negatively with days of abstinence in the BACLAD study. Total ghrelin plasma levels decreased in abstinent patients under baclofen. Acylated ghrelin levels increased in relapsed patients under baclofen and under placebo. Abstract: The orexigenic hormone ghrelin is involved in the regulation of food intake and energy balance. Previous findings suggest its involvement in the modulation of mesolimbic reward pathways, thus potentially being relevant in the pathophysiology of substance use disorders such as alcohol dependence. In the present study, we assessed plasma levels of total and acylated ghrelin within the BACLAD trial, where alcohol-dependent patients received individually titrated high-dose baclofen (30–270 mg/d) within a randomized, placebo-controlled design. Plasma levels of total ghrelin and acylated ghrelin were measured at baseline, during treatment with individually titrated high-dose baclofen and after termination of the study medication within a timeframe of up to 20 weeks. Multivariate longitudinal non-parametric analysis revealed that plasma levels of total ghrelin significantly decreased in the group of abstinent patients receiving high-dose baclofen. In addition, plasma levels of total ghrelin correlated negatively with days of abstinence during treatment with high-dose baclofen. Plasma levels of acylated ghrelin increased during the study in the group of relapsed patients under baclofen and placebo treatment. These findings suggest that the long-term response to baclofen treatment in alcohol use disorder (AUD) might be monitored by assessing total and acylated ghrelin plasma levels.